Phrasal Verb Vocabulary Teaching in the Album Niki’s Moonchild Using Quizizz - Vica Amifa Utami; Arso Setyaji; Laily Nur Affini (Lingua Franca, 2022)
The first goal of this study is to determine whether using Quizizz to teach vocabulary influences the teacher's preparation for lessons. 2. Describe the several categories of lesson plans utilized in implantation instruction. 3. choose the answer with the fewest phrasal verbs and the one that is the most accurate. In this study, the researcher employed descriptive qualitative research methods. This study focuses on students in class XI SMA N 2 Rembang, which the researcher may have employed in this preliminary study. Phrasal verbs can be used in the song lyrics from the albums Quizizz and Niki's Moonchild to gauge students' proficiency on phrasal verb tests. According to the experts, the CD features ten tracks and some additional phrasal verbs. The study's findings are as follows: arrangements made by researchers to use songs from Niki Moonchild's album as a teaching tool for phrasal verb vocabulary in the eleventh grade at SMA N 2 Rembang. Teachers will be using Quizizz to ask students questions. The teacher prepares active speakers to listen to songs, students listen to music for the purpose of listening to music, and preparation takes the form of employing song media as a teaching instrument. Since the lecture material will be shown on the LCD in the classroom, a laptop used for learning media must have working speakers. Additionally, the teacher creates handouts for the class that incorporate song lyrics with the phrasal verbs they will study. To make it simpler for students and teachers, this study also uses Quizizz's learning resources; the researcher needed two days in the classroom to implement the lesson plan for the students in the eleventh grade. Phrasal verbs were introduced on the first day of class and were then taught using songs from Niki Moonchild's limited album. Phrasal verb instruction continued the following day by having students listen to songs and search the words for phrasal verbs; students complete a quiz on Quizizz about the phrasal verbs found in the song lyrics, from which it can be determined which phrasal verbs they are already familiar with and which ones they are unfamiliar with. The result, which is well-known, is a warm-up exercise for vocabulary they are unfamiliar with, namely, look at.